2014
DOI: 10.1542/peds.2013-4024
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Limited View Follow-up Skeletal Survey

Abstract: BACKGROUND AND OBJECTIVE: Reducing radiation exposure to minimize risk has been emphasized in recent years. In child abuse, the risk of missing occult injuries is often believed to outweigh radiation risk associated with skeletal surveys. Our hypothesis was that there would be no clinically significant difference in results from a limited view, follow-up skeletal survey (SS2) protocol, which omits spine and pelvis views unless these views have findings on the initial skeletal survey (SS1), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…With the evidence of potential radiation risks, some authors have considered the performance of a limited follow‐up skeletal survey. A study by Hansen et al, looking at 534 cases of suspected NAI, found that a limited follow‐up skeletal survey, omitting the spine and pelvic views, missed 0.2% of new findings. The authors noted no clinically significant difference between the complete and the limited view follow‐up skeletal surveys.…”
Section: Resultsmentioning
confidence: 99%
“…With the evidence of potential radiation risks, some authors have considered the performance of a limited follow‐up skeletal survey. A study by Hansen et al, looking at 534 cases of suspected NAI, found that a limited follow‐up skeletal survey, omitting the spine and pelvic views, missed 0.2% of new findings. The authors noted no clinically significant difference between the complete and the limited view follow‐up skeletal surveys.…”
Section: Resultsmentioning
confidence: 99%
“…This is not an insignificant change in diagnosis. In fact, the change in diagnostic decision from reversing social risk is a more significant change in diagnostic decisions than has been documented with follow-up skeletal surveys, a strongly recommended diagnostic test in the evaluation of child physical abuse [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This number is not insignificant and is consistent with other studies, which have reported the rates of new information identification to be between 8% and 46%. 10 , 11 , 18 , 19 Of those that received FUSS, 2 children were admitted to the hospital, and 3 children had change of disposition. One child was admitted after the identification of new rib fractures, and the other was admitted for possible skull fracture for further evaluation and a safe disposition.…”
Section: Discussionmentioning
confidence: 99%